KONSEP DIRI SEORANG DA'I - Noormawanti Noormawanti; Iswati Iswati (Jurnal Bimbingan Penyuluhan Islam, 2019)
The concept of self is an understanding of the attitude of the individual towards himself so that it results in the interaction of two or more people. Self-concept is a factor that communicates with others. The concept of self is the views and attitudes of individuals towards themselves, characteristics and individual and self-motivation. The self-view includes not only individual strengths but also weaknesses and even failures. This self-concept is psychological, social and physical. Self-concept is our views and feelings about ourselves, which include physical, psychological and social aspects. The concept of self is not just a descriptive picture, but also an assessment of ourselves, including what we think and how we feel. Anita Taylor defines self-concept as "all you think and feel about you, the entire complex of beliefs and attitudes you hold abaout yourself '. Human behavior is a product of their interpretation of the world around them through social interaction. Behavior is often a choice as a feasible thing to do based on how it defines the existing situation. The definition they give to other people, situations, objects and even themselves determines their behavior. So it is individuals who are considered active to regulate and determine their own behavior and environment. While the core of the individual is consciousness (consciousness). self-development depends on communication with others, which shape or influence themselves